ENVIRONMENTAL CONSIDERATIONS - SOCIETY OF PETROLEUM ENGINEERS (Estados Unidos SPE, 1992)
INCLUDED ARE THE HIGHEST QUALITY PAPERS THAT COVERED THE VARIETY OF ENVIRONMENTAL ISSUES FACED BY THE INDUSTRY TODAY. IN MAKING THE FINAL SELECTION, EACH COMMITTEE MEMBER INDEPENDENTLY RATED THE PAPERS REVIEWED. THE RATINGS WERE THEN COMBINED INTO A TOTAL
SPE reprint series No. 37
Keywords: INGENIERIA PETROLERA-ASPECTOS MEDIOAMBIENTALES; PERFORACION DE POZOS